2018
DOI: 10.3390/tropicalmed4010007
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in Asia: Opportunities for One Health Management

Abstract: Clostridium difficile is a ubiquitous spore-forming bacterium which causes toxin-mediated diarrhoea and colitis in people whose gut microflora has been depleted by antimicrobial use, so it is a predominantly healthcare-associated disease. However, there are many One Health implications to C. difficile, given high colonisation rates in food production animals, contamination of outdoor environments by use of contaminated animal manure, increasing incidence of community-associated C. difficile infection (CDI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 92 publications
(149 reference statements)
1
12
0
Order By: Relevance
“…In our study, RT-126, -033, -078 and -010 turned out to be the most common ribotypes, each isolated from more than one farm. This finding is in accordance with what we have reported in calves in Italy [ 17 ] and is consistent with the literature, which indicates that these ribotypes as the most common ones in neonatal calves and piglets in Europe and Asia [ 15 , 24 , 34 , 40 , 41 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, RT-126, -033, -078 and -010 turned out to be the most common ribotypes, each isolated from more than one farm. This finding is in accordance with what we have reported in calves in Italy [ 17 ] and is consistent with the literature, which indicates that these ribotypes as the most common ones in neonatal calves and piglets in Europe and Asia [ 15 , 24 , 34 , 40 , 41 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, our study demonstrated that multiple C. difficile genotypes are circulating in the Asia-Pacific region and exhibit unique molecular characteristics at each site. C. difficile isolates with the same STs may be transmitted between different regions through food trade and travel in the Asia-Pacific region as previously reported [26]. Further studies focusing on analysis of whole-genome sequences combined with epidemiological data are required to investigate genetic relationship between different sites for the same STs.…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, an increasing number of studies has evaluated CDI epidemiology in Asia [12,26]. These have suggested that CDI is a very much under-recognized problem in Asia owing to poor clinical awareness among physicians [12].…”
Section: Discussionmentioning
confidence: 99%
“…Due to RT039 being non-toxigenic, it is usually not reported from human clinical samples (53, 54), however, it is a relatively common RT found in the environment in Australia although greater resistance to any antimicrobial agents has never been reported (55). Non-toxigenic C. difficile strains are highly prevalent in Asia and many of these strains are resistant to multiple antimicrobials, possibly due to inappropriate antimicrobial use in the region (56). These C. difficile RT039 strains may be of Asian origin and could have either acquired AMR genes via horizontal gene transfer from other microbes in the host intestine or from the consortium of pathogenic/commensal microbes in WWTPs.…”
Section: Discussionmentioning
confidence: 99%